Problems and prospects for livestock industry development in the context of digitalization of the agro-industrial complex in the region (based on the materials of the Republic of Bashkortostan of the Russian Federation) - Z. T. Nasretdinova; A. M. Khazieva; A. R. Nasretdinova (Вестник университета)
The current state and prospects of livestock breeding development in the Republic of Bashkortostan in the conditions of active digitalization of the agro-industrial complex have been analyzed. Despite the desire to introduce innovative technologies, the process faces a number of obstacles that require a comprehensive solution for sustainable development of the industry. The key problems have been highlighted, such as lack of a uniﬁed digital platform, low level of digital competencies, ﬁnancial constraints, lack of a uniﬁed strategy, and resistance to digital transformation. Prospects for livestock farming digitalization development in the region have been considered, such as smart livestock farms development through automated systems for climate control, feeding, milking, and animal health monitoring, use of sensors and the Internet of Things, artiﬁcial intelligence application for data analysis, yield forecasting, feeding and treatment processes optimization, development of a single digital platform for information exchange between farmers, veterinary services, fodder suppliers, and other participants, and development of a single digital platform for the exchange of information among farmers, veterinary services, feed suppliers, and other stakeholders. The important role of the state and the regions in digital livestock farming development has been emphasized, including ﬁnancial support, legal framework implementation, and infrastructure and research development. Emphasis has been placed on the fact that livestock breeding digitalization in the Republic of Bashkortostan has great potential for increasing efﬁciency and competitiveness of the industry, but its implementation requires comprehensive measures aimed at overcoming existing problems and creating favorable conditions for new technologies implementation.